First report of the plant fossils from the Manas National Park, Assam, India - Mehrotra, R.C.; Basumatary, S.K.; Bera, S.K.; Srivastava, Gaurav; Sarma, G.C.; Baruah, C.K. (Journal of Palaeosciences, 2011)
Plant fossils, mainly leaf impressions, are described for the first time from the Tipam Group of rocks exposed at Subankhata Locality in Manas National Park in Baksa District of Assam. Two new fossil leaves showing affinities with Parashorea stellata Kurz and Shorea ovalis (Korth.) Bl. respectively of the family Dipterocarpaceae, along with a fern frond of Cyclosorus resembling C. proliferus (Retz.) Tard. and C. Chr. of the family Thelypteridaceae are described from the present assemblage. In addition, impressions of a monocot stem and a seed-like structure are also reported. These plant fossils indicate Middle-Late Miocene age and existence of rain forest in the region during the period of deposition of the rock successions.